Aplikasi Pengelolaan Inventaris Barang Berbasis Web Pada Pondok Pesantren Darul Muta’allimin Kota Tasikmalaya - Miftah Farid Adiwisastra (Fakultas Teknik Universitas Hamzanwadi, 2022)
Managing inventory of goods in educational institutions must gain serious attention because the quality of educational institutions is extremely affected by the availability of facilities and infrastructure and the management of supporting goods inventory. Darul Muta'allimin Islamic Boarding School, in Kota Tasikmalaya, is an Islamic educational institution utilizing a Microsoft Excel application spreadsheet to manage the inventory of goods. However, they frequently encountered several problems while operating it, such as untidy goods data archives and challenges of reporting inventory data. For this reason, employing applications remained demanding to manage inventory data. The waterfall method was adopted to develop an application. The application was cultivated based on the Codeigniter framework (web-based) and the bootstrap with a Mysql database to be more responsive. The results revealed that the developed application was able to manage the inventory of goods, including facilities and infrastructure department. It occurred due to its supporting features, such as the features of borrowing goods, returning goods, and automatic report generation features